Associations between PTSD symptoms and other psychiatric symptoms among college students exposed to childhood sexual abuse: a network analysis - Yu Jin; Shicun Xu; Yinzhe Wang; Hui Li; Xiaofeng Wang; Xi Sun; Yuanyuan Wang (European Journal of Psychotraumatology, 2022)
Background: Childhood sexual abuse (CSA) is one of the prevalent forms of trauma experienced during childhood and adolescence. Previous research underscores its associations with depression, anxiety, post-traumatic stress disorder (PTSD), and psychosis. Objective: This study examined symptom connections between depression, anxiety, PTSD, and psychosis while simultaneously investigating whether these connections differed by gender among CSA survivors. Methods: A large-scale, cross-sectional study among 96,218 college students was conducted in China. Participants’ CSA was measured by the Childhood Trauma Questionnaire-Short Form (CTQ-SF). Participants’ PTSD, psychosis, depression, and anxiety were measured by the Trauma Screening Questionnaire (TSQ), the Psychosis Screener (PS), the nine-item Patient Health Questionnaire (PHQ-9), and the 7-item Generalized Anxiety Disorder Scale (GAD-7), respectively. Network analysis was used to explore the potential associations between these symptoms and to compare the sex differences in the symptoms model. Results: Among participants who suffered from CSA, females were more likely from left-behind households, while males were more likely from households with a high annual income (P < .001, Cohen’s W = 0.07). In addition, compared to male victims, female victims were more likely to report depression, anxiety, and PTSD (P < .001, Cohen’s d≈0.2), while male victims were more likely to report psychosis (P < .001, Cohen’s d = 0.36). Results from network estimation showed that psychosis, depression, anxiety, and PTSD symptoms were positively correlated. Moreover, psychosis had a stronger connection with PTSD symptoms, including hypervigilance, intrusive thoughts, and physiological and emotional reactivity. Conclusions: The current study explores the associations between PTSD symptoms and psychiatric symptoms among college students exposed to CSA using a network analysis approach. These crucial symptoms of PTSD may have potential connections to psychosis. Target intervention and strategy should be developed to improve mental health and quality of life among these CSA victims. Furthermore, longitudinal studies are warranted to advance our understanding of PTSD and psychosis.